Typology of Chao Phraya Dock Alley Area in Bangkok - Laddaklom, Panatpan (Journal of Social Sciences and Humanities Research in Asia, 2020)
Academic article on Classification of Soi Tha Nam Chao Phraya area in Bangkok. The objective is to study the classification of the area of Soi Chao Phraya in Bangkok. From Rama VII Bridge to Rama 9 Bridge, total distance of approximately 57 kilometers, using the survey method and processed by the Geographic Information System program. The study indicated that the area of Soi Tha Nam Chao Phraya in Bangkok can be classified according to the physical characteristics of the vacant space and can be accessed in 6 types, namely (1) Soi Tha Nam, the type of traffic parallel to the water 7 locations (2) Soi Tha Nam, open area type 7 locations (3) Soi Tha Nam, the type of traffic convergence 29 locations (4) Soi Tha Nam Sala port type 14 locations (5) Soi Tha Nam, Soi Ferry Pier 10 locations, and (6) Soi Tha Nam, an open-air area beside the alley Ferry port 4 locations. Which the highest amount of the waterfront area is Soi Tha Nam, the type of traffic convergence Followed by the pavilion pier type. The area of ​​the waterfront with the least amount is Soi Tha Nam, an open-air area near the ferry pier. Which is different and the type of area in Soi Tha Nam Chao Phraya will be Benefits for continuing education Including design, improvement, restoration and set policies to be consistent with the physical context of each area.